Diversity of herpetofauna and mammals on reclamation land PT. Refined Bangka Tin Bangka - Ratna Sari Hasibuan; Ken Dara Cita; Suwandi Raharjo; Agus Seftian Pracahyo; Fari Indarto; Tanya Zurmie (JURNAL SAINS NATURAL, 2021)
The success indicators of land reclamation can be seen in the presence of plants and animals. The more types of plants and animals that can live and reproduce, the better the condition of the land ecosystem. One of the indicators is the presence of herpetofauna and mammals, so this study aims to determine the diversity of wild animals consisting of herpetofauna, in this case, are reptiles and amphibians, and to determine the diversity of mammals in the area of PT. Refined Bangka Tin (PT. RBT). The research method was the Visual Encounter Survey (VES) for collecting herpetofauna data and the Path Transect method for collecting data on mammals. The results showed that seven species of reptiles were found with a diversity of 1.51, while there were three types of amphibians with a diversity of 1.04. The diversity of reptiles and amphibians based on the Shannon-Wiener diversity index is moderate. There are four species of mammals with a diversity of 1.12 based on the Shannon-Wiener diversity index value that the diversity of mammals is moderate.Keywords: herpetofauna, diversity, reclaimed land, mammalsKeanekaragaman herpetofauna dan mamalia pada lahan reklamasi  PT. Refined Bangka Tin, Bangka ABSTRAK Suatu perusahaan dikatakan berhasil mengelola lahan reklamasinya ditandai dengan adanya flora dan fauna. Semakin tinggi keanekaragaman flora dan fauna pada lahan reklamasi maka semakin baik keadaan ekosistem pada lahan reklamasi tersebut.    Salah satu fauna yang terdapat pada lahan reklamasi adalah herpetofauna dan mamalia, sehingga tujuan dari penelitian ini adalah untuk mengetahui keanekaragaman satwa liar yang terdiri dari herpetofauna dalam hal ini adalah reptil dan amfibi serta untuk mengetahui keanekaragaman mamalia di kawasan PT. Refined Bangka Tin (PT. RBT). Metode penelitian adalah Visual Encounter Survey (VES) untuk pengambilan data herpetofauna dan metode Transek Jalur untuk pengambilan data mamalia.  Hasil penelitian adalah satwa reptil ditemukan sebanyak 7 jenis dengan keanekaragaman 1,51, sedangkan amfibi ditemukan sebanyak 3 jenis dengan keanekaragaman sebesar 1,04.  Keanekaragaman reptil dan amfibi yang berdasar pada indeks keanekaragaman Shannon-Wiener adalah sedang.  Satwa mamalia ditemukan sebanyak 4 jenis dengan keanekaragaman sebesar 1,12 termasuk sedang berdasar nilai indeks keanekaragaman Shannon-Wiener.Kata kunci : herpetofauna, keanekaragaman, lahan reklamasi, mamalia